Sustained Reduction in Bloodstream Infections in Infants at a Large Tertiary Care Neonatal Intensive Care Unit. (February 2016) - Neill, Sara; Haithcock, Sarah; Smith, P. Brian; Goldberg, Ronald; Bidegain, Margarita; Tanaka, David; Carriker, Charlene; Ericson, Jessica E.
Abstract : Background: Bloodstream infections (BSI) cause significant morbidity and mortality among hospitalized infants. Purpose: Reduction of BSIs has emerged as an important patient safety goal. Implementation of central line insertion bundles, standardized line care protocols, and health care provider education programs have reduced BSI in NICUs around the country. The ability of large tertiary care centers to decrease nosocomial infections, including BSI, has been demonstrated. However, long-term BSI reductions in infants are not well documented. We sought to demonstrate that a low incidence of BSI can be maintained over time in a tertiary care NICU. Results: Baseline BSI incidence for infants admitted to the NICU was 5.15 and 6.08 episodes per 1000 infant-days in 2005 and 2006, respectively. After protocol implementation, the incidence of BSI decreased to 2.14/1000 infant-days and 2.44/1000 infant-days in 2008 and 2009, respectively. Yearly incidence remained low over the next 4 years and decreased even further to 0.20 to 0.45 infections per 1000 infant-days. This represents a 92% decrease in BSI over a period of more than 5 years. Implications for Practice: Implementation of a nursing-led comprehensive infection control initiative can effectively produce and maintain a reduction in the incidence of BSI in infants at a large tertiary care NICU. Implications for Research: Additional research is needed to effectively expand prevention of central line-associated BSIs to BSIs of all etiologies.